2008
DOI: 10.1542/peds.2007-0113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asthma Education on Children's Use of Acute Care Services: A Meta-analysis

Abstract: Providing pediatric asthma education reduces mean number of hospitalizations and emergency department visits and the odds of an emergency department visit for asthma, but not the odds of hospitalization or mean number of urgent physician visits. Health plans should invest in pediatric asthma education or provide health professionals with incentives to furnish such education. Additional research is needed to determine the most important components of interventions and compare the cost-effectiveness of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
96
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(113 citation statements)
references
References 44 publications
(93 reference statements)
8
96
1
8
Order By: Relevance
“…13,[29][30][31] Indeed, pediatric patients with asthma benefit from the utilization of a comprehensive medical home that provides continuity of care. 27,[32][33][34][35] Recent multicenter data have shown that asthma was in the top 10 admission diagnoses in pediatric patients, with the highest readmission rate of 10.6% within the first year after discharge. 5,36 These studies suggest that targeting care coordination for ambulatory care-sensitive conditions, such as asthma, may also have an impact on health care expenditures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[29][30][31] Indeed, pediatric patients with asthma benefit from the utilization of a comprehensive medical home that provides continuity of care. 27,[32][33][34][35] Recent multicenter data have shown that asthma was in the top 10 admission diagnoses in pediatric patients, with the highest readmission rate of 10.6% within the first year after discharge. 5,36 These studies suggest that targeting care coordination for ambulatory care-sensitive conditions, such as asthma, may also have an impact on health care expenditures.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Another limitation is the potentially confounding activity of the Asthma Task Force, which not only focused on compliance with asthma core measures but also on asthma education of the caretakers, which has been shown to reduce ED visits and hospitalizations. 34 It is therefore difficult to ascertain the individual effect of compliance with core measures without considering this additional component. Finally, reported ED utilization rates are only for the KMCWC and do not include ED visits to other hospitals in the Honolulu area.…”
Section: Discussionmentioning
confidence: 99%
“…O programa Criança que Chia, além de disponibilizar a corticoterapia inalatória em larga escala, investe na capacitação das equipes e promove acompanhamento clínico e grupos de discussão, com enfoque na educação sobre a doença 9,10,[25][26][27][28][29][30] . Programas de educação em asma aumentam a qualidade de vida dos pacientes e reduzem o número de hospitalização e atendimentos de emergência, que são onerosos ao sistema de saúde e, muitas vezes, evitáveis se a asma for manejada apropriadamente [25][26][27][28][29][30] .…”
Section: Discussionunclassified
“…Many well-designed clinical and prevention-oriented interventions in various settings have been able to demonstrate short-term reductions in asthma morbidity for individuals and small groups of participants in controlled settings (Coffman et al, 2008; National Heart Lung and Blood Institute 2007). However, these interventions often fail to have an impact on a larger scale.…”
Section: Introductionmentioning
confidence: 99%